Analysis of entries into the penalty area as a performance indicator in soccer - Ruiz-Ruiz, C.; Fradua, L.; Fernández-Garcia, A.; Zubillaga, A. (European Journal of Sport Science, 2013)
This study examines entries into the penalty area as a performance indicator that distinguishes between winning, drawing and losing soccer teams. It assesses whether entries into the penalty area are influenced by match status, a player's dismissal and the respective quality of the competing teams. Two observers analysed the relation between defensive and offensive strategies and their scoring consequences for all 64 matches played in the 2006 World Cup. Kappa values ranged between 0.93 and 0.98 for intra-reliability and between 0.88 and 0.98 for inter-reliability. It was found that winning teams received significantly fewer entries into their own penalty area (mean=41.42, s=11.86) than drawing (mean=50.07, s=14.75) and losing teams (mean=47.23, s=12.14). Teams that received more entries into their own penalty area than the opposing team were significantly more likely to concede a goal (P <0.001). Teams losing by one (mean=0.41, s=0.21), two (mean=0.42, s=0.26) or more than two goals (mean=0.34, s=0.13) received significantly fewer entries into the penalty area per minute than teams winning by one (mean=0.55, s=0.27) or two goals (mean=0.59, s=0.39). Teams with fewer players on the pitch received significantly more entries into the penalty area per minute than teams with more (mean=0.22, s=0.07) or the same number (mean=0.14, s=0.05) of players. Based on these results, it is suggested that teams should enter the opposing team's penalty area but should not allow their opponents to do the same. These results also highlight the significance of the dismissal of a player.